The Effect of Backloading Instructions on Eyewitness Identification from Simultaneous and Sequential Lineups. Issue 6 (November 2016) - Carlson, Curt A.; Carlson, Maria A.; Weatherford, Dawn R.; Tucker, Amanda; Bednarz, Jane
Summary: The sequential lineup is multifaceted, including serial presentation of faces, multiple decisions, and often backloading (indicating to an eyewitness that a lineup contains more photos than there actually are). We evaluated the effect of backloading instructions on response bias and sensitivity with an eyewitness identification paradigm. Importantly, we included an 'undisclosed' condition that provided no information to participants about the number of lineup members to expect. Experiment 1 ( N = 780) tested sequential lineups; Experiment 2 ( N = 532) tested simultaneous lineups. As predicted, signal detection analysis showed that backloading induced participants to be more conservative in choosing from both lineup types, but did not affect d′ . We conclude that the criminal justice system should be mindful of this shift in response bias, as it has implications for both guilty and innocent suspect identifications. Copyright © 2016 John Wiley & Sons, Ltd.